Central Nervous System Involvement of Rhabdomyosarcoma: A Single Institution Experience. Issue 2 (March 2019) - Moreira, Daniel C.; Macy, Margaret E.; Cost, Carrye R.; Greffe, Brian S.; Garrington, Timothy P.
Abstract : The incidence of central nervous system (CNS) involvement in patients with rhabdomyosarcoma (RMS) is low, and the outcome is dismal. We present a single institution analysis of CNS involvement of pediatric RMS. In 59 patients, the prevalence of CNS involvement was 11.9% (7 patients), higher than prior reports. Of the 6 deaths from disease, all had rapid progression, with a median survival of 14 days. The higher incidence could be secondary to treatment modifications or more sensitive detection. These findings are useful for decisions at the time of CNS involvement and could lead to modifications for future RMS clinical trials.